In Vitro Susceptibility of Clostridium difficile Isolates to Cefotaxime, Moxalactam, and Cefoperazone - Greenfield, Ronald A. (1982)
The in vitro susceptibility of 20 isolates of Clostridium difficile to cefotaxime, moxalactam, and cefoperazone was determined by a standard agar dilution method. The median minimal inhibitory concentrations were 64, 32, and 32 μg/ml for cefotaxime, moxalactam, and cefoperazone, respectively.